Urgensi Tasawuf terhadap Kehidupan Masyarakat Modern - Moh. Solehuddin; Ahmad Baidowi (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2020)
People's lives today seem to grow and develop materialistic and hedonistic traits, this symptom is characterized by making material a benchmark for achieving success and happiness. People are competing to find and get as much material as possible. This kind of encouragement has an impact on the tendency of people to act without control to get what they want by justifying all means without regard for others, loss of social care, individualistic, materialistic, capitalist and hedonic tendencies. Sufism in social life has a significant influence in solving existing social problems and diseases, the practices contained in the teachings of Sufism will guide a person in navigating the life of the world to become a wise, wise and professional human being in social life and provide spiritual and social values ??that clear. The form of teaching offered to cleanse the soul and social disease in Sufism can be carried out in three stages, namely Takhalli to cleanse oneself of despicable traits, from outward immorality and inner immorality that pollutes the human heart such as envy and envy, prejudice, pride, pride, showing off, short-tempered and other despicable qualities. Tahalli purifies or adorns oneself with commendable qualities, by being physically and mentally obedient. Tajalli revelation of supernatural light for the heart.